2022
DOI: 10.1186/s12868-022-00723-x
|View full text |Cite
|
Sign up to set email alerts
|

Chronic, acute and protocol-dependent effects of exercise on psycho-physiological health during long-term isolation and confinement

Abstract: Exercise could prevent physical and psychological deteriorations, especially during pandemic times of lock-down scenarios and social isolation. But to meet both, the common exercise protocols require optimization based on holistic investigations and with respect to underlying processes. This study aimed to explore individual chronic and acute effects of continuous and interval running exercise on physical and cognitive performance, mood, and affect and underlying neurophysiological factors during a terrestrial… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 84 publications
0
4
0
Order By: Relevance
“…[52][53][54] Increased plasma IGF-1 is beneficial for health 55,56 ; in contrast, decreased IGF-1 is seen in aging human plasma and is related to sarcopenia 57,58 by reducing DNA synthesis and altering the dynamics of mitochondria. 59,60 Like other myokines, the serum levels of IGF-I can increase, [61][62][63][64] decrease, [65][66][67] or remain unchanged 68 as a result of various types and intensities of exercise. We confirmed that IGF-1 expression and secretion was the highest in 2% static loading of myoblasts as compared with 5% and 10%.…”
Section: Discussionmentioning
confidence: 99%
“…[52][53][54] Increased plasma IGF-1 is beneficial for health 55,56 ; in contrast, decreased IGF-1 is seen in aging human plasma and is related to sarcopenia 57,58 by reducing DNA synthesis and altering the dynamics of mitochondria. 59,60 Like other myokines, the serum levels of IGF-I can increase, [61][62][63][64] decrease, [65][66][67] or remain unchanged 68 as a result of various types and intensities of exercise. We confirmed that IGF-1 expression and secretion was the highest in 2% static loading of myoblasts as compared with 5% and 10%.…”
Section: Discussionmentioning
confidence: 99%
“…Participants were screened thoroughly by the National Aeronautics and Space Administration (NASA). Inclusion/exclusion criteria required that the participants originate from various cultures and nationalities, have no prior experience with spaceflight, and include both males and females; all participants were in excellent health—they passed a drug screen, physical exam, and psychological assessment, and had no history of neurological, CV, integumentary, musculoskeletal, or gastrointestinal problems (Abeln et al., 2022 ; Saveko et al., 2022 ; Yamazaki, Antler, Casale, et al., 2021 ; Yamazaki, Rosendahl‐Garcia, et al., 2022 ). The studies were approved by the Institutional Review Board of the NASA (4‐month study and 8‐month study) with primary oversight, and by the Institutional Review Boards of the University of Pennsylvania (4‐month study) and Rush University Medical Center (8‐month study).…”
Section: Methodsmentioning
confidence: 99%
“…Participants were screened thoroughly by the National Aeronautics and Space Administration (NASA). Inclusion/exclusion criteria required that the participants come from various cultures and nationalities, have no prior experience with space flight, and include both males and females; all participants passed a drug screen and a physical exam ensuring they were in excellent health with no history of neurological, CV, integumentary, musculoskeletal, or gastrointestinal problems, and passed a psychological assessment (Yamazaki et al, 2021(Yamazaki et al, , 2022bAbeln et al, 2022;Saveko et al, 2022). The studies were approved by the Institutional Review Board of the NASA (4-month study and 8-month study) with primary oversight, and also by the Institutional Review Boards of the University of Pennsylvania (4-month study) and Rush University Medical Center (8-month study).…”
Section: Participantsmentioning
confidence: 99%